Adhesive product made from pyrolysis oil via polymerization

By polymerizing the energy-polymerized components in the pyrolytic oil to form an oligomeric liquid resin, the problem of limited value-added path of pyrolytic plastic oil is solved, and the performance of adhesive is improved.

CN119546719AInactive Publication Date: 2025-02-28TOTALENERGIES SE
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202380053748.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-14
Filing Date
2023-07-13
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize pyrolytic plastic oil, especially because it contains a large amount of impurities and olefins, resulting in limited value-added paths.

Method used

By polymerizing the polymerizable components in the pyrolyzed oil, a low molecular weight oligomeric liquid resin is generated as a tackifier in the adhesive composition, and its processing oil effect in the adhesive is utilized.

Benefits of technology

The value-added of pyrolytic plastic oil is achieved, and the generated oligomeric liquid resin has low viscosity and good compatibility, which can effectively improve the performance of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention relates to an adhesive composition comprising an elastomer and tackifying resins wherein one of the tackifying resins comprises a liquid resin prepared from a liquid waste polymer, preferably pyrolytic oil, via polymerization, preferably via cationic polymerization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to adhesive compositions comprising a liquid resin derived from the polymerization of a pyrolysis oil. In particular, the present disclosure relates to the polymerization of polymerizable components in the pyrolysis oil, preferably via polymerization to obtain a low molecular weight oligomeric product that can be used as a liquid tackifier that can function as a process oil in the adhesive composition. Background Art

[0002] Due to its increased availability, low-cost gases are replacing liquids as feedstocks for the production of ethylene in the steam cracking process. As a result, lower amounts of C5 dienes are produced, leading to a shortage of this monomer for the production of tackifying resins. Therefore, there is a need for alternative monomers for enhancing or even completely replacing current petroleum-based dienes to produce cost-effective and readily available tackifying resins.

[0003] Most of the discarded plastics are transferred to landfills or incinerated, with a smaller portion being transferred to recycling. However, due to the impact of regulations, there is a strong demand to limit the discarded plastics in landfills. On the other hand, it is becoming increasingly difficult to dispose of the discarded plastics in landfills. Therefore, there is a need for recycled discarded plastics.

[0004] A possible route for recycling plastics is via plastic pyrolysis. However, pyrolysis plastic oil obtained from plastic pyrolysis is generally not easy to value-add. Pyrolysis plastic oil contains a large amount of impurities and a large amount of dienes and olefins.

[0005] US 3,809,680 describes a hard resin prepared by reaction of formaldehyde and pyrolysis oil obtained by destructive distillation of waste rubber vulcanizates and its preparation. The resin can be used as a tackifier to be used in elastomers.

[0006] US 3,933,720 relates to a polychloroprene type adhesive composition comprising an acid-modified hydrocarbon resin, polychloroprene and suitable adhesives such as metal oxides and anti-aging agents and, if desired, known resins for polychloroprene type adhesives such as alkylphenol resins and petroleum resins, and volatile solvents.

[0007] US2012 / 0214592 relates to an adhesive composition made from an elastomer and a tackifying resin. The tackifying resin includes a farnesene polymer or copolymer having the following properties: i) less than 10% by weight of volatile organic compounds; ii) an Mn between 300 Da and 1000 Da; iii) an Mw between 400 Da and 3000 Da; iv) an Mw / Mn between 1.00 and 3.00; v) a Tg between -50°C and 20°C; and vi) a viscosity between 400,000 cP and 1,000,000 cP at 25°C. A method of making a farnesene-based polymer or copolymer comprises combining a farnesene monomer and a solvent and optionally adding one or more comonomers selected from dienes, branched mono-olefins, and vinyl aromatics to provide a monomer feed, and polymerizing the monomer feed by combining it with a Friedel-Crafts initiator in a container. The farnesene-based polymer or copolymer tackifier may be combined with one or more elastomers and one or more other tackifiers to form an adhesive composition.

[0008] FR 3,116,279 relates to a process for producing hydrocarbon resins from a raw material containing rubber chips, said process comprising at least one pyrolysis step and a resin synthesis step.

[0009] There therefore exists a need for the valorization of those pyrolyzed plastic oils. More specifically, there clearly exists a need for the valorization of the olefins and dienes present in the pyrolyzed plastic oils. Summary of the invention

[0010] The object of the present disclosure is to provide a value-added route for olefins and dienes present in pyrolysis oil. More specifically, the object of the present disclosure is to convert polymerizable materials present in pyrolysis oil into valuable oligomeric products. In particular, it has been found that adhesive compositions can be produced from liquid resins prepared from liquefied waste polymers.

[0011] It has been found that the oligomeric products prepared by pyrolysis oil and especially by pyrolysis plastic oil are particularly advantageous. In fact, such oligomeric products present relatively low viscosity. Under the situation of low viscosity, it is easier to handle oligomeric products. Especially, it is easier to mix liquid resin or oligomeric products with other components. Especially, less mechanical energy is needed to mix liquid resin or oligomeric products with other components. Another advantage of liquid resin or oligomeric products is the content of its aromatics. In fact, having some aromatics allows to improve the compatibility of some other components in liquid resin or oligomeric products and adhesive composition.

[0012] According to a first aspect, the adhesive composition comprising an elastomer and one or more tackifying resins is notable in that one of the one or more tackifying resins comprises a liquid resin prepared via polymerization from liquefied waste polymers, preferably pyrolysis oils.

[0013] As will become clearer below, the liquid resin is an oligomeric product.

[0014] In a preferred embodiment, the adhesive composition elastomer is selected from styrene-isoprene block copolymers, polyacrylate resins, polyethylene vinyl acetate (EVA) resins, polystyrene butadiene resins, random styrene butadiene (SBR) copolymers, styrene-butadiene block copolymers, styrene-isoprene-butadiene-styrene (SIBS) copolymers, styrene-ethylene-propylene-styrene (SEPS) copolymers, styrene-ethylene-butylene-styrene (SEBS) block copolymers, amorphous poly-olefin (APO) resins, and mixtures thereof.

[0015] In some embodiments, the elastomeric adhesive composition content ranges from 1 to 90 weight %.

[0016] In some embodiments, the content of tackifying resin derived from liquid waste polymer ranges from 1 to 75 wt %; preferably 5 to 60 wt %.

[0017] In some embodiments, when 1 When measured by H NMR, the liquid resin (i.e., the oligomeric product) exhibits an olefin content of up to 20.0 wt %. Preferably, the olefin content of the liquid resin ranges from 0.1 to 20.0 wt %, preferably from 0.3 to 15.0 wt %, more preferably from 0.5 to 10.0 wt %, 0.8 to 5.0 wt %.

[0018] In some embodiments, when 1 The liquid resin (i.e., the oligomeric product) exhibits an aliphatic content in the range of 15 to 100 wt % when measured by H NMR; preferably in the range of 40.0 to 99.5 wt %; more preferably in the range of 50.0 to 99.0 wt %; even more preferably in the range of 70.0 to 98.5 wt %; and most preferably in the range of 80.0 to 98.0 wt %.

[0019] In one or more embodiments, when 1 The liquid resin (ie, the oligomeric product) exhibits an aromatic content in the range of 0.3 to 45.0 wt %; preferably in the range of 0.5 to 40.0 wt %; more preferably in the range of 0.8 to 30.0 wt %; and even more preferably in the range of 1.0 to 20.0 wt % when measured by H NMR.

[0020] In an embodiment, the liquid resin (i.e., the oligomeric product) has a viscosity measured using a Brookfield viscometer at 30° C. ranging from 10 to 50,000 cps; preferably ranging from 10 to 50,000 cps; more preferably ranging from 10 to 10,000 cps; even more preferably ranging from 10 to 4000 cps; and most preferably ranging from 10 to 2500 cps.

[0021] In some embodiments, the liquid resin (i.e., the oligomeric product) has a number average molecular weight (Mn) measured using gel permeation chromatography and polystyrene calibration in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 140 to 1,000 g / mol; even more preferably 150 to 800 g / mol; most preferably 180 to 700 g / mol; or 200 to 650 g / mol; or 250 to 550 g / mol.

[0022] In some embodiments, the liquid resin (i.e., the oligomeric product) has a weight average molecular weight (Mw) measured using gel permeation chromatography and polystyrene calibration in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 150 to 3,500 g / mol; and even more preferably 200 to 2,000 g / mol.

[0023] In some embodiments, the liquid resin (i.e., the oligomeric product) has a z-average molecular weight (Mz) in the range of 100 to 100,000 g / mol; preferably 120 to 85,000 g / mol; more preferably 150 to 70,000 g / mol; and even more preferably 200 to 50,000 g / mol, as measured using gel permeation chromatography and polystyrene calibration.

[0024] In some embodiments, the liquid resin (ie, the oligomeric product) has a Mw / Mn ranging from 1.0 to 10.0; preferably 1.0 to 5.0; more preferably 1.0 to 4.0; and even more preferably 1.1 to 2.8.

[0025] In a preferred embodiment, the liquid resin (i.e., the oligomeric product) contains a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin (i.e., the oligomeric product) contains a comonomer, and the comonomer is or contains styrene.

[0026] In an embodiment, the liquid resin (ie, the oligomeric product) comprises the comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.

[0027] In some embodiments, the liquid resin (i.e., the oligomeric product) is a wax and / or exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 18 to 32°C; more preferably in the range of 20 to 30°C; and even more preferably in the range of 21 to 29°C.

[0028] In an embodiment, the liquid resin (i.e., the oligomeric product) is a resin and / or exhibits a glass transition temperature (Tg) of below -20°C; preferably in the range of -60°C to -25°C; more preferably -50°C to -30°C; and even more preferably -49°C to -35°C when measured by differential scanning calorimetry.

[0029] According to a second aspect, the present disclosure relates to an article comprising a substrate and an adhesive composition according to the first aspect; the adhesive composition is applied to at least one surface of the substrate, wherein the substrate is selected from a tape and a label.

[0030] According to a third aspect, the present disclosure is directed to a coated article comprising the adhesive composition according to the first aspect; the adhesive composition is applied to at least one of wood, nonwoven fabric, and book binding.

[0031] According to a fourth aspect, the present disclosure is directed to a box and case assembly line comprising an adhesive station, wherein the adhesive station dispenses the adhesive composition according to the first aspect.

[0032] According to a fifth aspect, the present disclosure relates to a process for preparing a liquid resin from liquefied waste polymers, the liquid resin being an oligomeric product and being suitable for preparing an adhesive composition according to the first aspect or being suitable for use in any product according to any one of the second to fourth aspects, the process being notable for the following steps:

[0033] a) providing a feed stream comprising liquefied waste polymer, wherein the feed stream comprises at least 0.1 wt % and at most 80 wt % diene, based on the total weight of the feed stream;

[0034] c) polymerizing the feed stream under polymerization conditions to obtain a first product stream comprising oligomeric products and purified liquefied waste polymer;

[0035] d) optionally, conducting a neutralization reaction by contacting the first product stream with a basic compound to obtain a neutralized product stream, and removing the basic compound from the neutralized product stream to obtain a second product stream;

[0036] g) separating the oligomeric products from the purified liquefied waste polymer.

[0037] In some embodiments, the liquefied waste polymer is pyrolyzed plastic oil. Preferably, step a) of providing a feed stream containing the liquefied waste polymer comprises a preliminary step of preparing the liquefied waste polymer, comprising:

[0038] a1) Provide waste plastic streams;

[0039] a2) pyrolyzing the waste plastic stream at a temperature of at least 200° C.;

[0040] a3) collecting the pyrolyzer effluent and separating it into a C1 to C4 hydrocarbon fraction, a fraction having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil;

[0041] a4) optionally sending the fraction with a boiling range above 350°C to a fluid catalytic cracking (FCC) unit, or a hydrocracking unit, a coker, or a visbreaker, or blending said fraction with a boiling range above 350°C in crude oil or in a crude oil fraction for further refining.

[0042] In one or more embodiments, the process further comprises a step b) of drying the feed stream to obtain a dried feed stream, wherein step b) is performed before step c) of polymerization, so that step c) of polymerization is performed on the dried feed stream. Preferably, step b) of drying is performed and it includes a sub-step b1) of decantation and / or centrifugation. More preferably, the first sub-step b1) is followed by a second sub-step b2) of drying using molecular sieves to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).

[0043] In some embodiments, the feed stream contains at least 75% by weight of liquefied waste polymer, based on the total weight of the feed stream.

[0044] Step c) comprises carrying out a polymerization reaction, preferably a cationic polymerization or a free radical polymerization or an anionic polymerization.

[0045] In a preferred embodiment, the polymerization reaction is a cationic polymerization; more preferably, the polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid.

[0046] In a preferred embodiment, the polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst, wherein the acidic catalyst is a Lewis acid selected from BF3, a complex of boron trifluoride, AICl3, SnCl4, ZnCl2, FeCl3 and TiCl3, an alkylaluminum chloride, H2SO4, or any mixture thereof; preferably, the acidic catalyst is or comprises boron trifluoride etherate.

[0047] In an embodiment, the acidic catalyst is present in a concentration ranging from 0.5 wt % to 5.0 wt %, based on the total weight of the feed stream and / or the polymerization reaction of step c) is carried out until the purified liquefied waste polymer has less than 5.0 wt % diene, based on the total weight of the first product stream.

[0048] In a preferred embodiment, the polymerization conditions of step (c) include a contact time ranging from 5 minutes to 5 hours; and / or a temperature ranging from 5 to 100°C at atmospheric pressure.

[0049] In an embodiment, the polymerization reaction of step c) is carried out in the presence of one or more comonomers; preferably, the one or more comonomers comprise vinyl aromatic and / or the one or more comonomers are present in a concentration of 1.0 to 25.0 wt %, based on the total weight of the liquefied waste polymer.

[0050] In some embodiments, the basic compound forms a basic stream; wherein the basic stream and the first product stream are contacted in a weight ratio ranging from 1:1 to 1:1,000.

[0051] In some embodiments, step d) is performed with a concentration of the basic compound ranging from 0.1 to 50.0 wt %, based on the total weight of the neutralized product stream.

[0052] In a preferred embodiment, step d) is performed and the basic compound:

[0053] - has a pKa in water in the range of 7.5 to 14; and / or

[0054] - is selected from LiOH, NaOH, CsOH, Ba(OH)2, Na2O, KOH, K2O, CaO, Ca(OH)2, MgO, Mg(OH)2, NH4OH, or any mixture thereof.

[0055] In an embodiment, step d) is performed in a continuous mode; and / or removing said basic compound from the neutralized product stream, to obtain a second product stream, is performed by decantation and / or by centrifugation.

[0056] In an embodiment, the process further comprises a step e) of washing the first product stream or the second product stream with a solvent to obtain a washed stream; preferably, the washing is carried out at a temperature ranging from 5°C to 95°C.

[0057] In a preferred embodiment, the solvent is selected from water or an acidic aqueous solution, which comprises:

[0058] - one or more organic acids selected from the group consisting of: citric acid ( )、Formic acid( ), acetic acid ( ), aminosulfonic acid ( ), and any combination thereof; and / or

[0059] - One or more inorganic acids selected from the group consisting of hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), phosphoric acid (H3PO4), and any combination thereof.

[0060] In some embodiments, washing is performed until the pH of the washed stream is in the range of 5.0 to 9.0; and / or washing is followed by decantation and / or centrifugation to separate the solvent from the washed stream.

[0061] In an embodiment, the process further comprises a step f) of filtering the stream obtained in the previous step to obtain a filtered stream, wherein the filtration is performed to remove solids from the first product stream or from the second product stream or from the washed stream, and / or to agglomerate remaining traces of solvent, if any; preferably, the filtration step is followed by a dehydration step.

[0062] In an embodiment, step g) of separating is performed via distillation or steam distillation or vacuum stripping or fractional distillation or any combination.

[0063] In a preferred embodiment, in the process after the separation step g), the purified liquefied waste polymer is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.

[0064] In a preferred embodiment, the liquefied waste polymer in the feed stream has a final boiling point of at most 700°C.

[0065] In a preferred embodiment, the feed stream contains from 0.1 to 50.0 wt %; preferably from 0.1 to 25.0 wt % of diene, based on the total weight of the feed stream.

[0066] According to a sixth aspect, the present disclosure provides an apparatus for performing the process described in the fifth aspect, wherein the apparatus is notable in that it comprises:

[0067] - polymeric part;

[0068] - optional neutralizing moiety;

[0069] - Separation parts;

[0070] wherein the polymerization section and the separation section are fluidly connected in series, and wherein the neutralization section, when present, is placed downstream of the polymerization section and upstream of the separation section.

[0071] Preferably, the device comprises:

[0072] - a pretreatment section comprising a pyrolysis unit, one or more separation units, and optionally a washing unit;

[0073] - a drying section comprising a decanter and / or a centrifuge; and / or molecular sieves;

[0074] - a polymerization section comprising one or more polymerization reactors; preferably loaded with an acidic catalyst;

[0075] - a neutralization section, a mixing reactor and optionally a separation unit comprising at least one selected from a decanter, a centrifuge and a filter;

[0076] - a washing section comprising a mixing vessel and a separation unit comprising a decanter and / or a centrifuge;

[0077] - A filtration section comprising a filter and optionally a molecular sieve.

[0078] - A separation section comprising a separation unit comprising one or more distillation columns.

[0079] In a seventh aspect, the present disclosure provides a method for producing an adhesive composition, comprising: producing an oligomeric product according to the process described in the fifth aspect; and mixing the collected oligomeric product and an elastomer to form an adhesive composition; wherein the oligomeric product is a liquid resin prepared from liquefied waste polymers and is used as a tackifying resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0080] Figure 1 A possible embodiment of the present invention is described. In this possible embodiment, the liquefied waste polymer is first optionally dried and sent to a cationic polymerization to convert dienes into oligomeric products. The effluent of the cationic polymerization is then sent to an optional treatment with an alkaline compound, followed by the removal of the alkaline compound and an optional washing step. After an optional filtering step, the various fractions are separated into various fractions according to boiling points. If the heavy fraction can be separated, it is sent to a conversion unit. The oligomeric products converted into resins can also be separated. If the remaining fraction of the purified plastic oil fraction exists, it can be sent to hydrotreatment or cracking or steam cracking to produce further polymerized olefins. The oligomeric products obtained can also be used as valuable resins.

[0081] Figure 2 A calibration curve for maleic anhydride concentration is presented.

[0082] Figure 3 The 1H NMR olefin content of the treated pyrolysis oils compared to the original pyrolysis oils of Examples 2 to 4 is presented.

[0083] Figure 4 The olefinic carbon stretching peak areas from the FTIR of Examples 2 to 4 are presented.

[0084] Figure 5 The viscosity of the adhesive formulation associated with Example 6 at 160°C is presented.

[0085] Figure 6 The 180° peel adhesion test on SS associated with Example 6 is presented.

[0086] Figure 7 The 180° peel adhesion test on HDPE associated with Example 6 is presented.

[0087] Figure 8 The 180° peel adhesion test on CC related to Example 6 is presented.

[0088] Fig. 9 Loop tack results on SS related to Example 6 are presented.

[0089] Fig.10 The loop quick bond results on HDPE related to Example 6 are presented.

[0090] Fig.11 The circular quick-tack results on CC related to Example 6 are presented.

[0091] Fig.12 The quick stick results on SS associated with Example 6 are presented.

[0092] Fig.13 The quick-stick results on HDPE related to Example 6 are presented.

[0093] Fig.14 The fast-tack results on CC related to Example 6 are presented.

[0094] Fig.15 Room temperature shear results on SS related to Example 6 are presented.

[0095] Fig.16 Room temperature shear results on Kraft Paper associated with Example 6 are presented.

[0096] Fig.17 SAFT results on SS related to Example 6 are presented.

[0097] Fig.18 SAFT results on kraft paper related to Example 6 are presented.

[0098] Fig.19 is an example of an apparatus according to the present disclosure.

[0099] Definition and Analytical Methods

[0100] For the purposes of this disclosure, the following definitions are provided:

[0101] As used herein, the term "alkane" or "alkanes" describes a non-cyclic branched or unbranched hydrocarbon with the general formula CnH2n+2, and is therefore composed entirely of hydrogen atoms and saturated carbon atoms; see, for example, IUPAC. Compendium of Chemical Terminology, 2nd edition (1997). The term "alkane" describes correspondingly unbranched alkanes ("normal-paraffins" or "n-paraffins" or "n-paraffins" or "paraffins") and branched alkanes ("iso-paraffins" or "iso-paraffins"), but does not include cycloalkanes (cycloalkanes). They are sometimes referred to by the symbol "HC-".

[0102] The term "olefin" or "alkene" as used herein relates to unsaturated hydrocarbon compounds containing at least one carbon-carbon double bond. They are sometimes referred to by the symbol "HC=".

[0103] The term "hydrocarbon" refers to alkanes (saturated hydrocarbons), cycloalkanes, aromatic hydrocarbons and unsaturated hydrocarbons together.

[0104] As used herein, the terms "comprising, comprises, comprised of" are synonymous with "including" or "containing", and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps. The term "comprising" also includes the term "consisting of".

[0105] The recitation of numerical ranges by endpoints includes all integers and, where appropriate, fractions included in the range (e.g., 1 to 5 may include 1, 2, 3, 4 when referring to, for example, a plurality of elements, and may also include 1.5, 2, 2.75, and 3.80 when referring to, for example, a measurement result). The recitation of endpoints also includes the recited endpoint values ​​themselves (e.g., 1.0 to 5.0 includes both 1.0 and 5.0). Any numerical range recited herein is intended to include all subranges incorporated therein.

[0106] The term "conversion" refers to the mole fraction (ie, percentage) of a reactant that is converted to one or more products. The term "selectivity" refers to the percentage of a reactant that is converted to a specified product.

[0107] The terms "wt %, "volume %" or "mole %" refer to the weight, volume or mole percentage of a component, respectively, based on the total weight, total volume or total moles of the material including the component. In a non-limiting example, 10 grams of a component in 100 grams of a material is 10% by weight of the component.

[0108] The term "naphtha" refers to the general definition used in the oil and gas industry. In particular, it refers to hydrocarbons derived from crude oil distillation having a boiling range of 15 to 250° C. when measured by ASTM D2887-22e1. Naphtha is substantially free of olefins because the hydrocarbons are derived from crude oil. Naphtha is generally considered to have a carbon number between C3 and C11, although in some cases the carbon number can reach C15. It is also generally recognized that the density range of naphtha is 0.65 to 0.77 g / mL.

[0109] The term "gas oil" refers to the general definition used in the oil and gas industry. In particular, it refers to hydrocarbons having a boiling point in the range of 250 to 350° C. when measured according to ASTM D7500-15 (2019).

[0110] The term "liquefied waste polymer" refers to any hydrocarbon liquid obtained from waste polymers, preferably obtained from waste plastics. In order to obtain such liquefied waste polymers, processes such as hydrothermal liquefaction or thermal pyrolysis or catalytic pyrolysis or steam pyrolysis or even pyrolysis in the presence of hydrogen can be used. Any polymer considered as waste is encompassed by the waste polymer, such as discarded polyethylene (PE), discarded polypropylene (PP), discarded polyethylene terephthalate (PET), discarded polyvinyl chloride (PVC), and other polymers such as those derived from discarded or used tires. The term "liquefied waste polymer" also encompasses "pyrolysis plastic oil".

[0111] The term "pyrolysis plastic oil" refers to the liquid product obtained once the discarded plastic has been thermally pyrolyzed. The pyrolysis process should be understood as a non-selective thermal cracking process. Pyrolysis involves breaking the polymer chain by heating. Pyrolysis does not decompose the polymer into its original monomers, but tends to produce a series of shorter chain compounds, which are similar to the mixture of hydrocarbons found in crude oil and oil products in many aspects. Catalysts are sometimes used to reduce the operating temperature. The pyrolyzed plastic can be of any type. For example, the pyrolyzed plastic can be polyethylene, polypropylene, polystyrene, polyester, polyamide, polycarbonate, etc. These liquefied waste polymers contain paraffin, iso-paraffin (isomeric-paraffin), diene, alkyne, olefin, cycloalkane and aromatic components. The liquefied waste polymer may also contain impurities such as organic chlorides, organosilicon compounds, metals, salts, oxygen-containing compounds, sulfur and nitrogen compounds, etc. The source of plastic is discarded plastic, without restrictions on the source of plastic or on the properties. The composition of the liquefied waste polymer depends on the type of pyrolyzed plastic. However, it is mainly composed of impurities and hydrocarbons having 1 to 50 carbon atoms.

[0112] The contents of paraffins, cycloparaffins, olefins and aromatics were determined according to the standardized method UOP990-11. This method uses two-dimensional gas chromatography (GCxGC) coupled to a flame ionization detector (FID).

[0113] The term diene value (DV) or maleic anhydride value (MAV) corresponds to the amount of maleic anhydride (expressed as iodine equivalents) that will react with 100 parts of oil under specific conditions. It is a measure of the conjugated double bonds in the oil. 1 mole of maleic anhydride corresponds to 1 conjugated double bond. A known method for quantifying dienes is UOP 32617: Diene value by maleic anhydride addition reaction. The term diene value (DV) refers to an analytical method by titration, expressed in g iodine / 100 g sample. The term maleic anhydride value (MAV) refers to an analytical method by titration, expressed in mg maleic acid / g sample. There is a correlation between MAV = DV * 3,863, since 2 moles of iodine correspond to 1 mole of maleic anhydride. For the examples presented, a specific method was used. The weight % of dienes presented in this application are obtained according to this specific method described in the examples section.

[0114] The term bromine number corresponds to the amount of bromine in grams reacted by 100 grams of a sample. This value indicates the amount of olefins in the sample. It is measured in grams of Br2 / per 100 grams of solution (gBr2 / 100 g), and can be measured, for example, according to method ASTM D1159-07 (2017).

[0115] The term bromine index is the number of milligrams of bromine that react with 100 grams of sample. It is measured in milligrams of Br2 / 100 g of solution (mgBr2 / 100 g) and can be measured, for example, according to method ASTM D2710-20.

[0116] The term boiling point used refers to the boiling point generally used in the oil and gas industry. They are measured at atmospheric pressure. The initial boiling point is defined as the temperature value when the first bubble of steam is formed. The final boiling point is the highest temperature that can be reached during a standard distillation. At this temperature, no more steam can be driven into the condensation unit. The determination of the initial boiling point and the final boiling point is known per se in the art. Depending on the boiling range of the mixture, they can be determined using various standardized methods, such as ASTM D2887-22e1, which relates to the boiling range distribution of petroleum fractions by gas chromatography. For compositions containing heavier hydrocarbons, ASTM D7169-20e1 can be used alternatively. The boiling range of the distillate can also be advantageously measured using ASTM D7500-15 (2019) or standard NF EN 15199-1. Due to the nature of the liquefied waste polymers, the preferred method for the measurement of the boiling point is method NF EN 15199-1. Depending on the method, differences of up to 10°C can be demonstrated. Therefore, the boiling points stated here should be considered with an absolute uncertainty of + / - 10°C.

[0117] Molecular weight: Mn (number average molecular weight), Mw (weight average molecular weight), Mz (z average molecular weight), and molecular weight distribution d (Mw / Mn) and d' (Mz / Mw) are determined by gel permeation chromatography (GPC). GPC is performed as follows.

[0118] Equipment: Agilent 1260 Series Degasser (Part No. G1322A); Agilent 1260 Series Isocratic Pump (Part No. G1310B); Agilent 1260 Series Autosampler (Part No. G1329B); Agilent 1260 Series Thermostatic Column Compartment (Part No. G1316A); Agilent 1260 Series Multi-Wavelength Detector (Part No. G1365C); and Agilent 1260 Series Refractive Index Detector (Part No. G1362A).

[0119] Column set: 1x Agilent ResiPore 50 x 4.6 mm guard column (Part No. PL1513-1300); and 2x Agilent ResiPore 250 x 4.6 mm 3 um particle size columns (Part No. PL1513-5300).

[0120] Software: Cirrus 3.3, ChemStation B04.03

[52] .

[0121] Solvent: THF stabilized with 250 ppm BHT

[0122] Flow rate: 0.45 ml / min.

[0123] Column chamber temperature: 40°C

[0124] Injection volume: 5 ml

[0125] Sample preparation: Weigh approximately 0.06 g of sample into a vial. Dissolve in 10 ml THF and filter through a 0.45 micron PTFE membrane. Run samples on the day of sample preparation.

[0126] Polystyrene calibration standards were used.

[0127] The molecular weight average used in establishing molecular weight / property relationships is the number average molecular weight (M n ), weight average molecular weight (M w ) and z-average molecular weight (M z ). These averages are defined by the following expressions and are calculated by M i Determination:

[0128]

[0129] Here N i and W i are the number and weight of molecules with molecular weight Mi, respectively.

[0130] The molecular weight distribution (MWD) was then calculated as Mw / Mn.

[0131] Crystallization temperature (Tc) and glass transition temperature (Tg) were measured using differential scanning calorimetry (DSC), TA Instruments Q2000 equipped with a liquid nitrogen cooling system (LNCS). The software was TA Instruments UniversalAnalysis 2000 version 4.5A. We used a temperature ramp with a ramp rate of 10°C / min.

[0132] As will be apparent to one skilled in the art from this disclosure, the particular features, structures, characteristics or embodiments may be combined in any suitable manner in one or more embodiments. DETAILED DESCRIPTION

[0133] It has been found that the use of Lewis acids such as Friedel-Crafts catalysts to polymerize polymerizable materials in pyrolysis oils, and in particular plastic pyrolysis oils containing dienes, results in polymerizable materials having low T g The formation of a low molecular weight liquid resin with low viscosity and some aromatic content. Other monomers such as branched mono-olefins, vinyl-aromatic or other dienes can be combined with the pyrolysis oil to provide additional monomer feed that can be copolymerized to change the properties and compatibility and impart the desired functionality to the resin.

[0134] The liquid resin comprises a homopolymer or copolymer resin based on low molecular weight pyrolysis oil obtained using a Friedel-Crafts catalyst and preferably has a low viscosity and some aromatic content.

[0135] The present disclosure provides adhesive compositions comprising an elastomer and one or more tackifying resins, notable in that one of the one or more tackifying resins comprises a liquid resin prepared via polymerization from liquefied waste polymers, preferably pyrolysis oils.

[0136] As will become clear further below, the liquid resin is an oligomeric product.

[0137] In a preferred embodiment, the adhesive composition elastomer is selected from styrene-isoprene block copolymers, polyacrylate resins, polyethylene vinyl acetate (EVA) resins, polystyrene butadiene resins, random styrene butadiene (SBR) copolymers, styrene-butadiene block copolymers, styrene-isoprene-butadiene-styrene (SIBS) copolymers, styrene-ethylene-propylene-styrene (SEPS) copolymers, styrene-ethylene-butylene-styrene (SEBS) block copolymers, amorphous poly-olefin (APO) resins, and mixtures thereof.

[0138] In some embodiments, the elastomeric adhesive composition content ranges from 1 to 90 weight %.

[0139] In some embodiments, the content of tackifying resin derived from liquid waste polymer ranges from 1 to 75 wt %; preferably 5 to 60 wt %.

[0140] In some embodiments, when 1 When measured by H NMR, the liquid resin (i.e., the oligomeric product) exhibits an olefin content of up to 20.0 wt %. Preferably, the liquid resin has an olefin content in the range of 0.1 to 20.0 wt %; preferably 0.3 to 15.0 wt %; more preferably, 0.5 to 10.0 wt %, 0.8 to 5.0 wt %.

[0141] In some embodiments, when 1 The liquid resin (i.e., the oligomeric product) exhibits an aliphatic content in the range of 15 to 100 wt % when measured by H NMR; preferably in the range of 40.0 to 99.5 wt %; more preferably in the range of 50.0 to 99.0 wt %; even more preferably in the range of 70.0 to 98.5 wt %; and most preferably in the range of 80.0 to 98.0 wt %.

[0142] In one or more embodiments, when 1The liquid resin (ie, the oligomeric product) exhibits an aromatic content in the range of 0.3 to 45.0 wt %; preferably in the range of 0.5 to 40.0 wt %; more preferably in the range of 0.8 to 30.0 wt %; and even more preferably in the range of 1.0 to 20.0 wt % when measured by H NMR.

[0143] In an embodiment, the liquid resin (i.e., the oligomeric product) has a viscosity measured using a Brookfield viscometer at 30° C. ranging from 10 to 50,000 cps; preferably ranging from 10 to 50,000 cps; more preferably ranging from 10 to 10,000 cps; even more preferably ranging from 10 to 4000 cps; and most preferably ranging from 10 to 2500 cps.

[0144] In some embodiments, the liquid resin (i.e., the oligomeric product) has a number average molecular weight (Mn) measured using gel permeation chromatography and polystyrene calibration in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 140 to 1,000 g / mol; even more preferably 150 to 800 g / mol; most preferably 180 to 700 g / mol; or 200 to 650 g / mol; or 250 to 550 g / mol.

[0145] In some embodiments, the liquid resin (i.e., the oligomeric product) has a weight average molecular weight (Mw) measured using gel permeation chromatography and polystyrene calibration in the range of 100 to 10,000 g / mol; preferably 120 to 5,000 g / mol; more preferably 150 to 3,500 g / mol; and even more preferably 200 to 2,000 g / mol.

[0146] In some embodiments, the liquid resin (i.e., the oligomeric product) has a z-average molecular weight (Mz) in the range of 100 to 100,000 g / mol; preferably 120 to 85,000 g / mol; more preferably 150 to 70,000 g / mol; and even more preferably 200 to 50,000 g / mol, as measured using gel permeation chromatography and polystyrene calibration.

[0147] In some embodiments, the liquid resin (ie, the oligomeric product) has a Mw / Mn ranging from 1.0 to 10.0; preferably 1.0 to 5.0; more preferably 1.0 to 4.0; and even more preferably 1.1 to 2.8.

[0148] In a preferred embodiment, the liquid resin (i.e., the oligomeric product) comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin comprises a comonomer, and the comonomer is or comprises styrene.

[0149] In an embodiment, the liquid resin (ie, the oligomeric product) comprises the comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.

[0150] In some embodiments, the liquid resin (i.e., the oligomeric product) is a wax and / or exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 18 to 32°C; more preferably in the range of 20 to 30°C; and even more preferably in the range of 21 to 29°C.

[0151] In an embodiment, the liquid resin (i.e., the oligomeric product) is a resin and / or exhibits a glass transition temperature (Tg) of below -20°C; preferably in the range of -60°C to -25°C; more preferably -50°C to -30°C; and even more preferably -49°C to -35°C when measured by differential scanning calorimetry.

[0152] The present disclosure also provides a process and apparatus for producing the oligomeric product. Figure 1 and the device Fig.19 The apparatus and process are described together herein.

[0153] A process for preparing a liquid resin from liquefied waste, the liquid resin being an oligomeric product and suitable for preparing an adhesive composition according to the present disclosure, the process comprising the following steps:

[0154] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;

[0155] c) subjecting the feed stream 1 to a polymerization reaction under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;

[0156] d) optionally, conducting a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;

[0157] g) separating the oligomeric products from the purified liquefied waste polymer.

[0158] exist Figure 1 In the preferred embodiment shown in FIG. 1 , a process for preparing a liquid resin from liquefied waste, wherein the liquid resin is an oligomeric product and is suitable for preparing an adhesive composition, comprises the following steps:

[0159] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;

[0160] b) optionally, drying feed stream 1 to obtain a dried feed stream 2;

[0161] c) polymerizing the feed stream 1 or the dried feed stream 2 under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;

[0162] d) optionally, conducting a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;

[0163] e) optionally, washing the first product stream 3 or the second product stream 5 with a solvent to obtain a washed stream 6;

[0164] f) optionally, filtering the stream obtained in the previous step to obtain a filtered stream 7, wherein the filtration is carried out to remove solids from the first product stream or from the second product stream 5 or from the washed stream 6, and / or to agglomerate remaining traces of solvent, if any;

[0165] g) separating the oligomeric product from the purified liquefied waste polymer.

[0166] In a preferred embodiment, a process for preparing a liquid resin from liquefied waste, wherein the liquid resin is an oligomeric product and is suitable for preparing an adhesive composition, comprises the following steps:

[0167] a) providing a feed stream 1 containing liquefied waste polymer, wherein the feed stream 1 contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream 1;

[0168] b) drying feed stream 1 to obtain a dried feed stream 2;

[0169] c) subjecting the dried feed stream 2 to a cationic polymerization reaction under polymerization conditions to obtain a first product stream 3 comprising oligomeric products;

[0170] d) performing a neutralization reaction by contacting the first product stream 3 with a basic compound to obtain a neutralized product stream 4, and removing the basic compound from the neutralized product stream 4 to obtain a second product stream 5;

[0171] e) washing the second product stream 5 with a solvent to obtain a washed stream 6;

[0172] f) filtering the washed stream 6 to obtain a filtered stream 7, wherein the filtering is performed to remove solids from the washed stream 6 and / or to agglomerate remaining traces of solvent, if any;

[0173] g) separating the oligomeric product from the purified liquefied waste polymer.

[0174] The present disclosure also provides an apparatus 100 for carrying out a process for preparing a liquid resin from liquefied waste, wherein the liquid resin is an oligomeric product and is suitable for preparing an adhesive composition, and the apparatus is notable in that it comprises:

[0175] - a polymerization section C comprising one or more polymerization reactors 23;

[0176] - an optional neutralizing part D;

[0177] - a separation section comprising a separation unit 32 comprising one or more distillation columns,

[0178] wherein the polymerisation section C and the separation section are fluidly connected in series, and wherein the neutralisation section D (when present) is located downstream of said polymerisation section and upstream of said separation section.

[0179] In some embodiments, the present disclosure also provides an apparatus 100 for carrying out a process for preparing a liquid resin from liquefied waste, the liquid resin being an oligomeric product and suitable for preparing an adhesive composition, the apparatus being notable in that it comprises:

[0180] - optional pretreatment part A;

[0181] - optional drying part B;

[0182] - a polymerization section C comprising one or more polymerization reactors 23;

[0183] - an optional neutralizing part D;

[0184] - an optional washing part E;

[0185] - an optional filtration section; and

[0186] - A separation section comprising a separation unit 32 comprising one or more distillation columns.

[0187] In an embodiment, the present disclosure also provides an apparatus 100 for carrying out a process for preparing a liquid resin from liquefied waste, wherein the liquid resin is an oligomeric product and is suitable for preparing an adhesive composition, and the apparatus is notable in that it comprises:

[0188] - a pretreatment section A comprising a pyrolysis unit 11 , one or more separation units ( 13 , 16 , 19 ) and optionally a washing unit 18 ;

[0189] - a drying section B comprising a decanter and / or a centrifuge 21; and / or a molecular sieve 22;

[0190] - a polymerization section C comprising one or more polymerization reactors 23; preferably loaded with an acidic catalyst;

[0191] - a neutralization section D, a mixing reactor 24 and an optional separation unit 26 comprising at least one selected from a decanter, a centrifuge and a filter;

[0192] - a washing section E comprising a mixing vessel 28 and a separation unit 30 comprising a decanter and / or a centrifuge;

[0193] - a filtration section comprising a filter and optionally a molecular sieve 31; and

[0194] - A separation section comprising a separation unit 32 comprising one or more distillation columns.

[0195] Feed stream 1 and step a) of providing feed stream 1 and pretreatment section A

[0196] The feed stream 1 used in the process contains liquefied waste polymer.

[0197] Preferably, the liquefied waste polymer is derived from pyrolysis of plastic waste 10, so that the liquefied waste polymer is pyrolysis plastic oil.

[0198] Therefore, in a preferred embodiment, step a) of providing the feed stream 1 comprises a preliminary step of preparing a liquefied waste polymer, said preliminary step comprising:

[0199] a1) providing a waste stream 10, which is preferably a waste plastic stream;

[0200] a2) pyrolyzing said waste stream 10 at a temperature of at least 200° C.;

[0201] a3) collecting a pyrolyzer effluent 12 and separating the pyrolyzer effluent into a C1 to C4 hydrocarbon fraction 14, a fraction 17 having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil;

[0202] In such a case, the apparatus 100 may comprise a pretreatment section A comprising a pyrolysis unit 11, one or more separation units (13, 16, 19) and an optional washing unit 18. Preferably, the pretreatment section A comprises one or more separation units selected from the following:

[0203] - A first separation unit 13, which is used to remove pyrolysis gases, including a gas-liquid separator

[0204] - a second separation unit 16 for removing the fraction having a boiling range above 350° C., comprising one or more distillation columns; and

[0205] - A third separation unit 19 for removing particles and colloids, comprising a filter and / or a centrifuge.

[0206] In some embodiments (not shown), the process further comprises a further preliminary step of treating the fraction with a boiling range above 350°C, and therefore further comprises a step a4): sending the fraction with a boiling range above 350°C to a fluid catalytic cracking (FCC) unit, or a hydrocracking unit, a coker, or a visbreaker; or blending the fraction with a boiling range above 350°C in crude oil or in a crude oil fraction for further refining.

[0207] In a preferred embodiment, the liquefied waste plastic mainly contains pyrolysis plastic oil. Pyrolysis plastic oil is produced by pyrolysis of plastic waste. Examples of pyrolysis processes for waste plastics are disclosed in US 8,895,790 or in US2014 / 228606 and in WO2016 / 009,333.

[0208] In the waste plastic pyrolyzer, mixed plastics (e.g., waste plastics 10) are placed in a pyrolysis unit or pyrolyzer. In the pyrolysis unit 11, the waste plastics are converted into pyrolysis products via pyrolysis, wherein the pyrolysis products 12 contain a gas phase (e.g., pyrolysis gas, mainly such as C1 to C4 gas, hydrogen (H2), carbon monoxide (CO), carbon dioxide (CO2)) and a liquid phase, wherein the liquid phase is pyrolysis plastic oil.

[0209] Plastic waste 10 may include post-consumer waste plastics, such as mixed plastic waste. Mixed plastics may include non-chlorinated plastics (e.g., polyolefins, polyethylene, polypropylene, polystyrene, copolymers, etc.), chlorinated plastics (e.g., polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), etc.), etc., or mixtures thereof. Generally, waste plastics 10 include long-chain molecules or polymer hydrocarbons. Waste tires may also be used. That is, waste plastics may also include used tires.

[0210] The pyrolysis unit 11 can be any suitable container configured to convert waste plastic into gas and liquid products (e.g., simultaneously). The container can be configured for gas phase, liquid phase, vapor-liquid phase, gas-solid phase, liquid-solid phase, or slurry phase operation.

[0211] The container may contain one or more beds of an inert material or a pyrolysis catalyst, including sand, zeolite, alumina, a catalytic cracking catalyst, or a combination thereof. Generally, the pyrolysis catalyst is capable of transferring heat to the components undergoing the pyrolysis process in the pyrolysis unit. Alternatively, the pyrolysis unit 11 may be operated without any catalyst (e.g., pure thermal pyrolysis).

[0212] The pyrolysis unit 11 can be operated in an adiabatic, isothermal, non-adiabatic, non-isothermal, or a combination thereof. The pyrolysis reaction of the present disclosure can be carried out in a single stage or in multiple stages. For example, the pyrolysis unit 11 can be two reactor vessels connected in series fluidly.

[0213] In a configuration (not shown) in which the pyrolysis unit includes two containers, the pyrolysis process can be divided into a first stage performed in a first container and a second stage performed in a second container and fluidly connected downstream of the first stage. As will be appreciated by those skilled in the art, and with the help of the present disclosure, the second stage can enhance the pyrolysis of the intermediate pyrolysis product stream flowing from the first stage into the second stage to obtain pyrolysis products flowing out of the second stage. In some configurations, the first stage can utilize thermal cracking of the waste plastic, and the second stage can utilize thermal cracking or catalytic cracking of the waste plastic to obtain pyrolysis products flowing out of the second stage. Alternatively, the first stage can utilize catalytic cracking of the waste plastic, and the second stage can utilize thermal cracking or catalytic cracking of the waste plastic to obtain pyrolysis products flowing out of the second stage.

[0214] In some configurations, the pyrolysis unit 11 may include one or more devices configured to convert the mixed plastic into gas and liquid products. The one or more devices may or may not contain inert materials or pyrolysis catalysts as described above. Examples of such devices include one or more of the following: a heated extruder, a heated rotary kiln, a heated tank reactor, a packed bed reactor, a bubbling fluidized bed reactor, a circulating fluidized bed reactor, an empty heated container, a closed heated surface where the plastic flows down the wall and cracks, a container surrounded by an oven or kiln, or any other suitable device that provides a heated surface to assist in cracking.

[0215] The pyrolysis unit 11 can be configured to perform pyrolysis (e.g., cracking), and in some aspects (e.g., where hydrogen is added to the pyrolysis unit), additionally hydrogenate components of the waste plastic stream fed to the pyrolysis unit. Examples of reactions that can occur in the pyrolysis unit 11 include, but are not limited to, isomerizing one or more normal paraffins to one or more iso-paraffins, selectively ring-opening one or more cycloparaffins to one or more iso-paraffins, cracking long chain length molecules to short chain length molecules, removing heteroatoms from hydrocarbons containing heteroatoms (e.g., dechlorination), hydrogenating coke generated in the process, or a combination thereof.

[0216] In one or more configurations of the pyrolysis unit 11, a headspace purge gas may be used in all or part of the pyrolysis stage (converting the waste plastic into liquid and / or gaseous products) to enhance the cracking of the plastic, produce valuable products, provide feed for steam cracking, or a combination thereof. The headspace purge gas may include hydrogen (H2), C1 to C4 hydrocarbon gases (e.g., alkanes, methane, ethane, propane, butane, isobutane), inert gases (e.g., nitrogen (N2), argon, helium, steam), etc., or a combination thereof. When the waste plastic contains chlorinated plastics, the use of a headspace purge gas assists in dechlorination in the pyrolysis unit. The headspace purge gas may be introduced into the pyrolysis unit to help remove volatiles entrained in the molten mixed plastics present in the pyrolysis unit.

[0217] A stream containing hydrogen (H2) may be added to the pyrolysis unit 11 to enrich the pyrolysis unit environment with H2, to assist in stripping entrained hydrogen chloride in the pyrolysis unit, to provide a local environment rich in hydrogen in the pyrolysis melt or liquid, or a combination thereof; for example, independently of the waste plastic 10 stream, via a stream containing H2 directly fed to the pyrolysis unit 11. In some aspects, H2 may also be introduced into the pyrolysis unit 11 along with the stream, provided that adequate safety measures are incorporated for hydrogen handling of the plastic feed.

[0218] The pyrolysis unit 11 can promote any reaction of the components of the waste plastic 10 stream in the presence of or with hydrogen. Reactions that can occur are such as the addition of hydrogen atoms to double bonds of unsaturated molecules (e.g., olefins), resulting in saturated molecules (e.g., paraffins, iso-paraffins, cycloalkanes). Additionally, or alternatively, the reactions in the pyrolysis unit can cause the breaking of bonds of organic compounds, with subsequent reactions and / or replacement of heteroatoms with hydrogen.

[0219] The use of hydrogen in the pyrolysis unit 11 can have the following beneficial effects: (I) reducing coke as a result of cracking, (II) maintaining the catalyst (if any) used in the process in an active state, (III) improving the removal of chlorides from the stream so that the pyrolysis products from the pyrolysis unit 11 are substantially dechlorinated relative to the waste plastic stream, which minimizes the chloride removal requirements in units downstream of the pyrolysis unit, (IV) hydrogenation of olefins, (V) reducing dienes in the pyrolysis products, (VI) helping to operate the pyrolysis unit 11 at a reduced temperature to achieve the same conversion level of the waste plastic 10 stream in the pyrolysis unit, or a combination of (I)-(VI).

[0220] The pyrolysis process in the pyrolysis unit 11 may be low-severity or high-severity.

[0221] The low-severity pyrolysis process can occur at a temperature of less than about 450°C; for example, at a temperature ranging from 250°C to 450°C, preferably 275°C to 425°C, more preferably 300°C to 400°C, and can produce a pyrolysis oil rich in mono- and di-olefins and significant amounts of aromatics.

[0222] The high-severity pyrolysis process can occur at a temperature equal to or greater than about 450°C; for example, at a temperature ranging from 450°C to 750°C, preferably 500°C to 700°C, and more preferably 550°C to 650°C, and can produce aromatic-rich pyrolysis oil and more gaseous products (compared to low-severity pyrolysis).

[0223] As will be appreciated by those skilled in the art, a high severity pyrolysis process will result in the formation of more olefins and diolefins. These olefins and diolefins cannot be easily recovered.

[0224] The pyrolysis product 12 can be collected as an effluent from the pyrolysis unit 11 and conveyed (e.g., flowed, e.g., via pumping, gravity, pressure difference, etc.) to a pyrolysis separation unit (i.e., a first separation unit 13). The pyrolysis product 12 can be separated in the pyrolysis separation unit into a pyrolysis gas 14 stream and a pyrolysis plastic oil further used in step a) of the present disclosure.

[0225] The first separation unit 13 may include any suitable gas-liquid separator, such as a steam-liquid separator, an oil-gas separator, a gas-liquid separator, a degasser, a scrubber, a collector, a flash drum, a compressor suction drum, a gravity separator, a centrifugal separator, a filter blade separator, a demister pad, a liquid-gas coalescer, a distillation tower, etc., or a combination thereof.

[0226] In a preferred embodiment, the pyrolyzed plastic oil is derived directly from the pyrolysis of plastic waste without further chemical conversion or separation.

[0227] In a preferred embodiment, the feed stream 1 contains only liquefied waste polymers, even more preferably only pyrolyzed plastic oils. Alternatively, the feed stream 1 contains at least 10% by weight; preferably at least 25% by weight, more preferably at least 50% by weight, even more preferably at least 75% by weight of liquefied waste polymers, based on the total weight of the feed stream 1.

[0228] The feed stream 1 may contain 100 wt %; preferably up to 95 wt %; more preferably up to 90 wt %; even more preferably up to 85 wt %, and most preferably up to 80 wt % of the liquefied waste polymer, based on the total weight of the feed stream 1. When the feed stream 1 contains less than 100 wt % of the liquid waste polymer, the remainder may be, for example, diluent or other hydrocarbons.

[0229] In a preferred embodiment, feed stream 1 exhibits a bromine number of at most 150 g Br2 / 100 g, preferably at most 100 g Br2 / 100 g; more preferably at most 80 g Br2 / 100 g, and even more preferably at most 50 g Br2 / 100 g, when measured according to ASTM D1159-07 (2017).

[0230] In a preferred embodiment, the liquefied waste polymer in feed stream 1 has a starting boiling point of at least 15° C. and a final boiling point of at most 700° C. Preferably, the final boiling point is at most 600° C.; more preferably 560° C., even more preferably 450° C., even more preferably 350° C., most preferably 250° C.

[0231] In some embodiments, step a) of providing feed stream 1 comprises one or more sub-steps of pre-treatment of the liquefied waste polymer.

[0232] In fact, depending on the source of the liquefied waste polymer, some pretreatment may be necessary. That is, before purifying the liquefied waste polymer in the process of the present invention, the following pretreatment of the liquefied waste polymer or feed stream 1 may be considered.

[0233] In a preferred embodiment, the liquefied waste polymer or feed stream 1 is pre-treated in a washing or desalting unit 18 to remove water soluble salts prior to treatment in the process of the present invention.

[0234] In another preferred embodiment, the liquefied waste polymer or feed stream 1 is pre-treated in a separation unit 19 to extract particles and colloids 20 by filtration, centrifugation or a combination of both techniques before being treated in the process of the present invention.

[0235] Optional step b) of drying feed stream 1 to obtain dried feed stream 2 and drying part B

[0236] In another preferred embodiment, the liquefied waste polymer or feed stream 1 is pretreated in a dehydration unit (i.e., a drying unit) before being treated in the process of the present invention to remove water from the hydrocarbon stream to reach a water content of less than 0.1% by volume, preferably less than 0.05% by volume according to ASTM D95-13 (2018), and even more preferably the liquefied waste polymer can be decanted.

[0237] Preferably, the feed stream 1 is dried before being sent to the polymerization unit. Step b) of drying may be followed by a sub-step b1) of decantation and / or centrifugation; preferably, sub-step b1) is followed by a sub-step b2) of drying using a molecular sieve 22 to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).

[0238] In such a case, the apparatus 100 may include a drying section B comprising:

[0239] - a decanter and / or a centrifuge 21; and / or

[0240] - Molecular sieve 22

[0241] Step c) of subjecting feed stream 1 or dried feed stream 2 to polymerization and polymerization part C

[0242] Step c) comprises carrying out a polymerization reaction, which is a cationic polymerization, a free radical polymerization or an anionic polymerization; preferably, the polymerization reaction is a cationic polymerization. Therefore, the polymerization part C comprises one or more polymerization reactors 23 loaded with a catalyst; preferably an acidic catalyst.

[0243] In an embodiment, the polymerization is an anionic polymerization. In such a case, the anionic polymerization is carried out using an anionic initiator containing an organolithium and is terminated by reaction with a selected proton donor terminator to form a filterable lithium salt.

[0244] In the embodiment where the polymerization reaction is a cationic polymerization, the apparatus comprises a polymerization section C comprising one or more polymerization reactors 23 loaded with an acidic catalyst.

[0245] In an embodiment, the polymerization is a free radical polymerization. In such a case, the free radical polymerization is carried out with an initiator for generating the initial free radicals that lead to monomer propagation, followed by termination via combination or disproportionation.

[0246] In a preferred embodiment, the polymerization reaction is a cationic polymerization. Therefore, preferably, step c) is carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid; preferably a Lewis acid in the form of a transition metal halide.

[0247] Friedel-Crafts catalysts are strong Lewis acid catalysts that polymerize monomers via a cationic polymerization mechanism. According to various embodiments of the present invention, examples of Friedel-Crafts catalysts that can be used to polymerize monomer feeds containing pyrolysis oil include, but are not limited to, boron trifluoride, aluminum chloride, tin tetrachloride, titanium trichloride, titanium tetrachloride, iron (III) chloride, aluminum tribromide, dichloromonoethylaluminum, and complexes thereof, such as boron trifluoride-phenol complexes, boron trifluoride-ethanol complexes, boron trifluoride-ether complexes, etc., especially boron trifluoride-phenol complexes and boron trifluoride-ethanol complexes. Friedel-Crafts catalysts may also include liquid aluminum chloride / hydrochloric acid / substituted aromatic complexes, the aromatics being, for example, o-xylene, mesitylene, ethylbenzene, isopropylbenzene, etc., such as short-chain or long-chain alkylbenzenes. The alkyl chain may be linear or branched, and may vary from 2 to 30 carbon atoms. Acidic liquid AICI, obtained as a by-product during the alkylation of benzene or any other substituted aromatic (toluene, xylene) with branched olefins, can also be used. Branched olefins can be produced via boron trifluoride oligomerization and fractionation of propylene (e.g., C 12 Olefins or C 24 Olefins can be alkylated with aromatics).

[0248] The most preferred Friedel-Crafts catalysts are AlCl3 and BF3.

[0249] Therefore, preferably, step c) is carried out in the presence of an acidic catalyst, which is a Lewis acid selected from BF3, a complex of boron trifluoride, AICl3, SnCl4, ZnCl2, FeCl3 and TiCl3, an alkylaluminum chloride, H2SO4, or any mixture thereof. It is understood that BF3 refers to BF3 in gaseous form. 3。 A particularly suitable complex of boron trifluoride is boron trifluoride etherate.

[0250] In an embodiment, step c) is performed in the presence of an acidic catalyst, the acidic catalyst being a Lewis acid, wherein the acidic catalyst concentration ranges from 0.5 wt % to 5.0 wt %, based on the total weight of the feed stream 1 .

[0251] In an embodiment, the reaction conditions include a contact time of at least 5 minutes to at most 5 hours. Preferably, step c) is carried out under an inert atmosphere, preferably under a N2 atmosphere.

[0252] The resins described herein can be prepared by a continuous solution polymerization process, wherein a Friedel-Crafts catalyst, optional comonomers, and a suitable aromatic or aliphatic hydrocarbon solvent, such as toluene, xylene, or heptane, are continuously added to a reactor vessel to form the desired homopolymer or copolymer. Alternatively, pyrolysis oil-based polymers can be prepared by a batch process, wherein all initiators, monomers, and solvents are combined together and mixed in a reactor. The acidic catalyst may also be a solid catalyst.

[0253] Preferably, during the continuous polymerization reaction, the mass flow rate of the catalyst feed is 0.01 to 20 wt %; preferably 0.1 to 5 wt %, and more preferably 0.1 to 3 wt %, based on the total mass flow rate of the monomer feed and the catalyst feed.

[0254] The reaction temperature of the mixture in the reactor vessel is also preferably maintained at a temperature of about -10 to 50°C (when BF is used as the Friedel-Crafts catalyst) and about 10 to 60°C (when AlCl3 is used).

[0255] The low molecular weight pyrolysis oil based homopolymer or copolymer resin according to an embodiment of the present invention is a liquid resin having a number average molecular weight between 100 and 10,000 g / mol and more preferably 250 and 4,000 g / mol when measured via gel permeation chromatography and converted using polystyrene calibration.

[0256] In a preferred embodiment, the cationic polymerization is carried out in the presence of an acidic catalyst, preferably selected from BF3, AlCl3, SnCl4 and TiCl3, ion exchange resins, Cl2AlEt, H2SO4, or any mixture thereof.

[0257] In an embodiment, at least one of AlCl3 and BF3 may be used to polymerize a monomer feed comprising pyrolysis oil and a comonomer, wherein the comonomer content of the monomer feed is <90 wt%, <40 wt%, <25 wt%, or <15 wt%, based on the total moles of monomers in the monomer feed. Preferably, the polymerization initiator is BF3.

[0258] In particular, the acidic catalyst may be a solid acidic catalyst. Preferred solid acidic catalysts include molecular sieves, such as zeolites or silicalite. The use of solid acidic catalysts is particularly advantageous. The solid acidic catalyst can be easily separated. When a solid acidic catalyst is used, the neutralization step d) and the washing step e) may not be required.

[0259] In an embodiment, step c) is carried out when the solid acid catalyst is a molecular sieve, preferably selected from the topological MFI, BEA, FAU, MEL, and the polymerization conditions include a range of 0.5 to 5.0 h -1 In a preferred embodiment, the molecular sieve contains one or more heteroatoms selected from Ti, Sn, Mo, W, Fe, Ni, Co, Cu, Zr, Hf, Nb and Ta.

[0260] In an embodiment, step c) is carried out with the solid acid catalyst being an ion exchange resin, preferably a sulfonic acid ion exchange resin such as Amberlyst A15 or A35, and the polymerization conditions include a range of 0.5 to 5.0 h -1 The ion exchange resin includes an acidic resin such as a + In a preferred embodiment, the ion exchange resin is Amberlyst 15.

[0261] In an embodiment, step c) is carried out when the solid acid catalyst is clay or activated clay, and the polymerization conditions include a range of 0.5 to 5.0 h -1 LHSV.

[0262] Optional neutralization step d) and neutralization part D

[0263] When a soluble acidic catalyst is used in step c) to produce the first product stream 3, it may need to be subjected to a neutralization step d1), preferably followed by a washing step d2).

[0264] Thus, in some embodiments, the apparatus 100 comprises a neutralization section D comprising a mixing reactor 24 and an optional separation unit 26 comprising at least one selected from a decanter, a centrifuge, and a filter.

[0265] Step d) is a neutralization step, which can be accomplished by adding a base directly to the first product stream 3. In such a case, a basic compound, generally a solid, is brought into contact with the first product stream 3, and the obtained mixture is then stirred for at least 1 second to at most 24 hours, preferably during at least 1 minute to at most 12 hours. After stirring, the remaining base in the form of a solid is separated from the liquid, which is the second product stream 5.

[0266] The neutralization step can also be accomplished by washing the first product stream 3 with a basic compound 25, which is a basic solution. A basic aqueous solution is preferred, and a basic aqueous solution containing NaOH and / or NH4OH is the most preferred type of solution. The basic solution is contacted and agitated for at least 1 second to at most 24 hours, preferably at least 1 minute to at most 12 hours. The mixture is then separated to remove the second product stream 5 (which is an organic phase) from the aqueous phase. Separation may, for example, include decantation. Decantation is known per se and includes separating the immiscible organic and aqueous phases with the aid of gravity.

[0267] The neutralization step can also be carried out by contacting one or more basic compounds 25, preferably alkali / alkaline earth metal containing bases, more preferably solid bases such as LiOH, NaOH, CsOH, Ba(OH)2, Na2O, KOH, K2O, CaO, Ca(OH)2, MgO, Mg(OH)2, or any mixture thereof, or any strong base alone or in mixture, and alkaline aqueous solution, with the first product stream 3, either simultaneously or sequentially. After agitation of at least 1 second to at most 24 hours, the solid, the organic phase, which is the second product stream 5, and the aqueous phase are separated.

[0268] In a more preferred embodiment, step d) is performed in a continuous mode, i.e., addition of fresh alkaline compound is performed at, for example, the inlet of the mixing reactor 24 to the first product stream 3, while the spent alkaline compound is removed at the outlet of the mixing reactor 24 to obtain the second product stream 5.

[0269] In a preferred embodiment, the basic compound comprises an alkali metal cation, an alkaline earth metal cation and a quaternary ammonium base, preferably selected from TMAOH, TEAOH, TBAOH, TPAOH, or any mixture thereof.

[0270] Optional washing step e) and washing part E

[0271] The washing step e) comprises washing the first product stream 3 or the second product stream 5 with a solvent 27 to obtain a washed stream 6. In some embodiments, the washing step e) is performed after the neutralization step d) to remove trace amounts of basic compounds 25. In such a case, the washing step is performed with a ratio of the second product stream 5 or optionally the neutralized product stream 4 to the solvent 27 ranging from 0.05 to 20.

[0272] For example, washing is performed at a temperature ranging from 5° C. to 95° C., preferably at atmospheric pressure. Washing may be performed in a continuous mode or in a batch mode.

[0273] In a preferred embodiment, the solvent is selected from water or an acidic aqueous solution containing one or more organic acids such as citric acid ( )、Formic acid( ), acetic acid ( ), aminosulfonic acid ( ), or the inorganic acid is hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), phosphoric acid (H3PO4), and any combination thereof.

[0274] For example, the acidic solution has a pH ranging from 0.1 to 6.9.

[0275] Washing is preferably performed until the pH of the washed stream 6 or optionally the second product stream 5 or the neutralized product stream 4 is in the range of 5.0 to 9.0, preferably in the range of 6.0 to 8.0, even more preferably in the range of 6.5 to 7.5.

[0276] Preferably washing is followed by decantation and / or centrifugation to separate the solvent 27 from the washed mixture 29 to produce a washed stream 6 .

[0277] In such a case, the apparatus 100 may include a wash section E comprising a mixing vessel 28 and a separation unit 30, including a decanter and / or a centrifuge.

[0278] Optional filtration step f) and filtration section

[0279] The process may comprise a filtration step f) comprising filtering the stream obtained in the previous step to obtain a filtered stream 7, wherein the filtration is performed to remove solids.

[0280] In the embodiment wherein the preceding step is a washing step e), the process may comprise a filtration step f), which comprises filtering the washed stream 6 (i.e. the stream obtained in the preceding step) to obtain a filtered stream 7, wherein the filtration is performed to remove solids from the washed stream 6, and / or to agglomerate remaining traces of solvent, if any.

[0281] In a preferred embodiment, the filtration comprises a first sub-step of filtration to remove solids and / or to agglomerate remaining traces of solvent (if any), preferably followed by a second sub-step of dehydration, preferably carried out using molecular sieves to achieve a water content of the filtered stream 7 of less than 0.1 vol.-%, preferably less than 0.05 vol.-% according to ASTM D95-13 (2018).

[0282] In such a case, the device 100 may include a filtration section including a filter (not shown) and optionally a molecular sieve 31 .

[0283] Separation step g) and separation portion

[0284] The process comprises a separation step g) to separate the oligomeric product 33 from the purified liquefied waste polymer 34 .

[0285] In a preferred embodiment, said step g) of separating is carried out via distillation or steam distillation or vacuum stripping or fractional distillation or any combination thereof.

[0286] Thus, the apparatus comprises a separation unit 32 comprising one or more distillation columns.

[0287] The oligomeric product 33 obtained can also be further used to be converted into valuable resins such as valuable resins. After the separation step g), the oligomeric product 33 can be collected and mixed with an elastomer, a curing agent and a filler to obtain a rubber composition, or used as a tackifying resin and mixed with an elastomer to form an adhesive composition.

[0288] If not already done in the pretreatment section, the process may include the step of separating and recovering a fraction having a boiling range above 350° C., preferably above 300° C. This fraction may be recovered from any one of the purified liquefied waste polymer 34, the filtered stream 7, the washed stream 6, the second product stream 5, the neutralized product stream 4, the first product stream 3, the dried feed stream, or the feed stream 1. Thus, the fraction having an initial boiling point of at least 350° C., preferably at least 300° C., may be removed and sent to an FCC unit, a hydrocracking unit, a coker, or a visbreaker, or the fraction having a boiling range above 350° C. may be blended in crude oil or in a crude oil fraction for further refining.

[0289] Preferably, after separation step g), the purified liquefied waste polymer 34 is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.

[0290] Production of adhesive compositions

[0291] The present disclosure also provides a method for producing an adhesive composition, comprising producing an oligomeric product according to the process of the fifth aspect, and mixing the recovered oligomeric product with an elastomer to form an adhesive composition; wherein the oligomeric product is a liquid resin prepared from liquefied waste polymers and is used as a tackifying resin.

[0292] Detailed description of adhesive composition

[0293] In a preferred embodiment, the present invention encompasses an adhesive composition comprising an elastomer, a tackifying resin, and notably, at least one of the tackifying resins may be a process oil. Thus, no process oil needs to be added. More preferably, the adhesive composition does not contain any process oil.

[0294] According to another preferred embodiment, the elastomer of the adhesive composition of the present invention can be selected from styrene-isoprene block copolymers, polyacrylate resins, polyethylene vinyl acetate (EVA) resins, polystyrene-butadiene resins, random styrene butadiene (SBR) copolymers, styrene-butadiene block copolymers, styrene-isoprene-butadiene-styrene (SIBS), styrene-ethylene-propylene-styrene (SEPS), styrene-ethylene-butylene-styrene (SEBS) block copolymers, amorphous poly-olefin (APO) resins, and mixtures thereof.

[0295] Adhesive compositions according to various embodiments of the present invention may also include processing oils. The example of processing oils includes but is not limited to paraffin, aliphatic-cycloparaffin aromatic resins, polyethylene glycol, petroleum, ester plasticizers, sulfurized vegetable oils, pine tar, phenolic resins, petroleum resins, polymeric esters and rosin. Processing oils can range from about 0 to about 50 % by weight, wherein the scope of about 5 to 35 % by weight is preferred, based on the gross weight of the adhesive resin in the adhesive composition. In a preferred embodiment, tackifying resins of the present invention work as a suitable substitute for processing oils.

[0296] The tackifying resin according to the present invention may be incorporated into the adhesive composition by any method known to those skilled in the art. For example, one or more tackifying resins may be added during compounding of the adhesive composition.

[0297] Exemplary conventional hot melt adhesives include styrene-isoprene-styrene (SIS) block copolymers, hydrocarbon (C5 or C5 / C9) tackifying resins, rosin ester tackifiers, and / or process oils. Tackifying resins derived from liquid resins obtained by polymerization of pyrolysis oil products can be used to replace all or part of the process oil and used together with the C5 or C5 / C9 tackifying resins or rosin ester tackifiers in the exemplary formulation. SIS block copolymers can be used in hot melt adhesives, such as those sold by Kraton Performance Polymers Inc. of Houston, Tex. under the trade name Kraton. C5 hydrocarbon tackifying resins can be used, such as those sold by Total Petrochemicals and Refining, Inc. of Houston, Tex. under the trade name Wingtack. Naphthenic process oils can also be used in hot melt adhesives, such as those sold by Nynas AB of Stockholm, Sweden under the trade name Nyflex.

[0298] As known to those skilled in the art, conventional hot melt adhesives may include a variety of other components, including but not limited to starch, wax, plasticizer, antioxidant, stabilizer, pigment, dye, antimicrobial agent, flame retardant, antistatic agent, or filler. For example, the hot melt adhesive may include the antioxidant Ethanox 310 sold by Albemarle Corporation of Baton Rouge, La.

[0299] The components of adhesive composition according to the present invention can be combined by any process known to those skilled in the art. For example, they can be introduced separately from each other, and separated or combined with any independent component of conventional adhesive composition. As a further example, tackifying resin can be introduced into the composition comprising styrene-isoprene-styrene (SIS) block copolymer and optionally hydrocarbon (C5-C9) tackifying resin. Process oil or process oil substitute, such as liquid resin or oligomeric product from pyrolysis oil can be added at last. Adhesive composition can be mixed with for example sigma blade mixer until it is uniform. Other methods of mixing include but are not limited to single screw or twin screw, and are equipped with mixer as conventional tank of anchor or turbine.

[0300] Example

[0301] Method for measuring diene content

[0302] Unless otherwise specified, the following method was used to determine the diene content in the pyrolyzed plastic oils in all examples.

[0303] The determination of the diene content is carried out by means of GPC with a UV detector. A given amount of maleic anhydride is added to the pyrolyzed plastic oil and reacted with the diene via a Diels-Alder reaction. The reduction of the UV-active MA peak in the chromatogram is monitored and used to determine the diene concentration. In a first step, a calibration curve is prepared. The equipment used is

[0304] Agilent 1260 Series Degasser (Part No. G1322A); Agilent 1260 Series Isocratic Pump (Part No. G1310B); Agilent 1260 Series Autosampler (Part No. G1329B); Agilent 1260 Series Thermostat Column Compartment (Part No. G1316A); Agilent 1260 Series Multi-Wavelength Detector (Part No. G1365C); and Agilent 1260 Series Refractive Index Detector (Part No. G1362A).

[0305] Column set: 1x Agilent ResiPore 50 x 4.6 mm guard column (Part No. PL1513-1300); and 2x Agilent ResiPore 250 x 4.6 mm 3 um particle size columns (Part No. PL1513-5300).

[0306] Software: Cirrus 3.3, ChemStation B04.03

[52] .

[0307] Solvent: THF stabilized by 250 ppm BHT, Flow rate: 0.45 ml / min.

[0308] Column chamber temperature: 40°C

[0309] Calibration: Polystyrene standards from Agilent EasiCal Standards

[0310] i) GPC-UV Calibration of Maleic Anhydride:

[0311] Samples of known concentration of maleic anhydride (MA) in THF were prepared and analyzed using GPC with a UV detector.

[0312] The chromatograms were analyzed for peak areas at 240 nm.

[0313] A plot of MA (ppm) versus peak area can generate a calibration curve ( Figure 2 ). The equation of the line can be used to determine the concentration of MA in the unknown solution.

[0314] ii) Preparation of samples for testing:

[0315] A 6 wt % solution of maleic anhydride in toluene was prepared.

[0316] 15 g of MA was added to 200 mL of toluene and heated to 55°C for 4 hours. The solution was then cooled and the volume was brought to 250 mL.

[0317] The solution was allowed to stand overnight and filtered the following day. This removed some of the undissolved MA that had precipitated.

[0318] Once prepared, the solution should be used within two weeks.

[0319] The concentration of the MA solution was checked using the equation from the GPC-UV calibration (Equation 1) as follows:

[0320]

[0321] Where PA is the peak area at 240 nm (15.8-16.6 min) (mV.s), and sample MF is the concentration of the sample , and Inj. Vol is the sample injection volume (uL). The equation 0.1586x + 0.3095 is the equation of the straight line from the MA calibration graph.

[0322] iii) Sample preparation and Diels-Alder (DA) reaction

[0323] 15 g of sample (pyrolysis oil) was weighed out and added to a 100 mL round bottom flask (RBF).

[0324] 20 mL of 6% MA in toluene solution and a stir bar were added to the 100 mL RBF with the sample.

[0325] Gently mix the solution, then remove (take out) 55-70 mg of the mixture and place into a 20 ml bottle. Record the exact amount of mixture added.

[0326] Add 9-10 g of THF to the 20 mL bottle, recording the exact amount of THF added.

[0327] The sample in THF in the 20 mL bottle will be used for the initial determination of MA to calculate the dienes. Note as Initial Value in the calculation. Run GPC-UV.

[0328] The mixture in a 100 mL RBF was then heated to reflux for 3 hours.

[0329] While refluxing, then place 55-70 mg of the solution into the second 20 mL bottle. Record the exact amount added.

[0330] Add 9-10 g of THF to the second 20 mL bottle, record the exact amount of THF added. This sample is used for the final determination of MA to calculate dienes. Note as final value in calculations. Run GPC-UV.

[0331] The amount of reacted and unreacted MA was determined.

[0332] Calculate the initial amount of MA using Equation 1 and the initial sample.

[0333] Calculate the final amount of MA using Equation 1 and the final sample.

[0334] Convert the result from ppm to %, and calculate the amount of MA consumed using Equation 2:

[0335]

[0336] Determine the diene % of the sample

[0337] To determine the diene content, the amount of MA (g) used during the DA reaction needs to be known.

[0338] 20 mL of 6% MA solution in toluene = 1.8 g MA and 16.3 g toluene

[0339] The percentage of C5H8 dienes and higher MW dienes was determined.

[0340] Integration of the 240 nm peak area from 13.5-16 minutes and 16-18.5 minutes of the pure sample from GPC-UV provides the peak area percentages of the higher Mw dienes and C5H8 dienes, respectively.

[0341] The Mw (g / mol) of the higher Mw dienes was determined using the Mw (g / mol) from GPC and normalized using the Mw of the C5H8 peak and 68 g / mol.

[0342] Equation 3 is used to determine the diene percentage.

[0343] Equation 3:

[0344] The following pyrolyzed plastic oils were used in the examples:

[0345] Pyrolysis Oil 1: It has a boiling point in the range of 50°C to about 480°C and a diene value of about 2.7%. The chlorine content is in the range of about 115 ppm, and the silicon content is expected to be in the range of about 15 ppm. The oxygen content is expected to be in the range of about 1 wt%. The nitrogen content is expected to be in the range of about 1150 wt ppm.

[0346] Pyrolysis Oil 2: A light fraction obtained by distillation of pyrolysis oil (produced by non-catalytic pyrolysis of mixed waste plastics) and having a boiling point ranging from about 50° C. to about 260° C. The water content is expected to be below 100 ppm by weight. The diene value is expected to be in the range of about 4.8%.

[0347] Pyrolysis Oil 3: A light fraction of non-catalytic pyrolysis plastic oil (obtained by fractional condensation of pyrolysis effluent) and having a boiling point ranging from <36°C to about 260°C. The oil has been decanted to ensure that the water content is below 100 ppm by weight. The diene value is expected to be in the range of about 7.8%.

[0348] Pyrolysis Oil 4: It has a boiling point in the range of 40°C to about 401°C and a diene value of about 2.1%. The chlorine content is expected to be in the range of about 270 ppm, and the silicon content is expected to be in the range of about 12 ppm. The oxygen content is expected to be in the range of about 0.3 wt%. The nitrogen content is expected to be in the range of about 1250 wt ppm.

[0349] Example 1. Production of oligomeric products using BF3

[0350] The pyrolysis oil based liquid resin was prepared by solution polymerization, wherein the catalyst and monomers were continuously fed into a reaction vessel, and boron trifluoride diethyl etherate was used as a catalyst, wherein the weight percentage of BF3 to the total feed was 1.15±0.25%.

[0351] The flow rates of monomer feed and Friedel-Crafts catalyst were controlled so that the combined mass flow of catalyst feed to monomer was about 2 to 3 wt%. The reaction temperature was maintained at 40°C throughout the polymerization and all steps were performed under a nitrogen blanket.

[0352] The initial amount of pyrolysis oil (total amount of ~ 10 weight %) is added to a round bottom flask (RBF) purged with nitrogen as reaction tail. The tail is then warmed to 40 ° C under nitrogen while stirring. The pyrolysis oil feed and Lewis acid catalyst (BF3-OEt2) are measured out in a single flask. If comonomer (i.e. styrene) is used, it is measured out and added to the flask with the pyrolysis oil feed. The pyrolysis oil and catalyst are fed into the reactor while maintaining a temperature of 40 ° C so that the catalyst is added with 2 to 3 weight % of the monomer, and the two feeds are added at about the same time. When the feed addition is completed, the mixture is stirred at 40 ° C for 45-60 minutes, then cooled to room temperature. Polymerization is carried out under a nitrogen blanket.

[0353] The reaction mixture was then transferred to a separatory funnel and washed three times with 0.1 M NHOH, discarding the aqueous phase. The organic mixture was then washed twice more with water, and the organic phase was transferred to a separate three-necked round-bottomed flask for distillation. During the washing period, there was an insoluble tarry-like residue that remained on the side of the reaction flask and separatory funnel. In all cases of purification, unless otherwise noted, a tarry residue was left.

[0354] The organic mixture is purged with nitrogen while being heated to 230°C and volatile organics are collected. Once the temperature reaches 230°C, distillation is continued until no more volatiles are distilled, at which time the nitrogen is replaced by steam. The volatiles collected before steam stripping are referred to as distillate. Liquid resin or oligomeric products and steam condensate are collected until minimal liquid resin or oligomeric products are collected. The collected liquid resin or oligomeric products are referred to as oily polymers. The remaining material after steam stripping is the resin / wax product polymerized during purification. The collected distillate is a purified pyrolysis oil with reduced dienes.

[0355] Table 1 shows the catalyst and comonomer amounts used for the polymerization and the final diene concentration of the distillate after purification. After polymerization, the diene content had been reduced to less than 0.5% in all cases and in some cases had been removed to undetectable levels.

[0356] Table 1. Initial and final diene concentrations.

[0357]

[0358] Example 2. Production of oligomeric products using aluminum chloride (AlCl3) as a catalyst.

[0359] Hexane (~10 wt % of total amount) was added to the RBF using nitrogen purge. AlCl catalyst (approximately 1.25 wt % of total feed) was then added to the hexane and warmed to 35°C while stirring under nitrogen. The pyrolysis oil feed was measured out in a single flask and fed at a rate of 2 mL / min. Upon completion of feed addition, the mixture was stirred at 35°C for 50 minutes and then cooled to room temperature. Polymerization was carried out under a nitrogen blanket.

[0360] The reaction mixture was then transferred to a separatory funnel and washed three times with 25% isopropanol aqueous solution (IPA), and the aqueous phase was discarded. The organic mixture was then washed twice more with water, and the organic phase was transferred to a separate three-necked round-bottom flask for distillation. The organic mixture was then distilled and steam stripped as in Example 1.

[0361] Example 3. Production of oligomeric products using Amberlyst 15 as catalyst.

[0362] The pyrolysis oil was added to the RBF and stirred under nitrogen while warming to 40°C. Amberlyst 15, about 1% by weight of the total feed, was added as a catalyst in two doses. Once the oil reached 40°C, an initial amount of Amberlyst 15 catalyst (2 / 3 of the total amount) was added, and then stirred at 40°C for 45 minutes under nitrogen. The remaining 1 / 3 of the catalyst was then added, and the reaction was stirred for another 75 minutes. The mixture was then cooled to room temperature and the catalyst was filtered. The organic mixture was then distilled and steam stripped as in Example 1.

[0363] Example 4. Production of oligomeric products using sulfuric acid (H2SO4).

[0364] The pyrolysis oil was added to the RBF and stirred at room temperature. Sulfuric acid, about 2.5% by weight of the total feed, was then added to the stirred pyrolysis oil and immediately released heat. The reaction was stirred until the temperature dropped back to room temperature. The acid was neutralized and the oil was washed with dilute sodium carbonate (2x) followed by water (2x). The oil was then distilled and steam stripped as in Example 1.

[0365] The following table summarizes the various amounts of Lewis acid catalyst used in Examples 2-4.

[0366] Table 2. Summary of the amount of Lewis acid catalyst used

[0367]

[0368] For Examples 2 to 4, the effect of the purification process via cationic polymerization was determined by Figure 2 and 3 The 82 MHz 1 H NMR and FTIR measurements. Comparison of the fraction attributable to olefinic protons in the pyrolysis oil with the same fraction after cationic polymerization shows that the fraction of olefinic protons decreases in the case of all acid catalysts used. Similar conclusions were drawn from Figure 3 It is found that, in the case of cationic polymerization, the conjugated olefin peak area is reduced. Examples 2 to 4 therefore demonstrate that, in the case of the catalysts AlCl3, Amberlyst 15 and sulfuric acid, cationic polymerization allows a reduction in the diene content.

[0369] Example 5. Characterization of oligomeric products

[0370] The resin or wax product derived from the pyrolysis oil is the result of using cationic polymerization on the pyrolysis oil. When the resin or wax is produced and separated, the resulting liquid hydrocarbon is then the purified pyrolysis oil. In those embodiments, the liquid oligomeric products are of various kinds. That is, the wax+product consists of the tarry residue remaining after the aqueous wash is dissolved in acetone / THF and added to the organic phase for distillation.

[0371] The separated residue remaining after distillation and steam stripping of the post-polymerization pyrolysis oil is either a resin or wax product, depending on the pyrolysis oil feed. The reaction conditions and product properties are shown in Table 3.

[0372] Table 3. Reaction conditions and product properties of polymerized oils

[0373]

[0374] As shown in Table 4, the properties of the oligomeric products depend on the pyrolysis oil feed. The aromatic content in the wax+ and wax products from pyrolysis oil 1 is relatively low, and these are highly saturated hydrocarbon products. The melting and crystallization temperatures of the wax+ and wax products are about room temperature. The polymerized resin and resin-styrene products from pyrolysis oil 2 contain a higher amount of aromatic content.

[0375] Table 4. Comparison of polymerized products and commercially available products.

[0376]

[0377] Example 6. Preparation of Adhesive Composition

[0378] The polymerized resin and wax products from pyrolysis oils 2 and 1 were evaluated against Wingtack 10 (WT10, our reference) as a processing aid in a base tape formulation consisting of:

[0379]

[0380] The adhesive composition was mixed in an open-top sigma blade mixer at 177°C (350°F) under a nitrogen blanket. All mixing times were kept at less than 60 minutes to minimize degradation of the styrene block copolymer (SBC). First, the SBC and BNX 1010 antioxidant (AO) were combined and crushed for 5-10 minutes until smooth. Resins were added incrementally over a few minutes to ensure good mixing and prevent separation; once all resins were added, the formulation was mixed for 20-30 minutes. Finally, processing aids were added slowly while mixing and then mixed for another 10 minutes. The adhesive was transferred to a suitable container coated with a release liner to facilitate easy removal when cooled.

[0381] The viscosity of the adhesive formulations was measured at 160°C and can be found in Figure 4 The viscosity of the formulations with the resin and wax were 24% and 48% less, respectively, than the formulation using Wingtack 10. The reduction in melt viscosity should allow a reduction in the temperature required for coating, which translates into energy savings.

[0382] Wingtack 10 is a petroleum derived resin and was selected as a control and is known to be g The results provide superior adhesion performance compared to process oils in block polymer PSAs without the migration or shelf life issues frequently associated with process oils. Thus, the performance of the pyrolysis oil based resins is better than or equal to that of the control, indicating improved performance over conventional process oils.

[0383] The adhesive was coated on 2 mil (50 micron) PET at a dry thickness of approximately 0.9 mil (22 micron). The adhesive coated PET was laminated to release paper and allowed to condition at 50% relative humidity and 23°C (73°F) for a minimum of 24 hours prior to initial testing. For aged sample testing, the adhesive coated PET laminated to release paper was placed in an oven at 70°C for 7 days prior to testing. One inch and half inch strips were cut and tested according to the method detailed by the Pressure Sensitive Tape Council (PSTC).

[0384] 180° peel adhesion testing was performed using one inch wide (2.54 cm) test specimens and stainless steel (SS), corrugated cardboard (CC), and high density polyethylene (HDPE) test substrates. All adhesion tests are reported in pounds per square inch (psi). Loop Quick Tack and Quick Tack tests were performed using the same three test substrates and are reported in psi. Room temperature shear testing was performed using 0.5" wide, 0.5" overlap (1 / 4" total) test specimens. 2 The test was conducted with a 0.5 kg weight and a SS plate and unbleached kraft paper secured to the test plate using double-sided tape. Heat resistance was determined by measuring the Shear Adhesion Failure Temperature (SAFT) and reported in °C. The test specimens for the SAFT determination were one inch wide and had a 1 inch 2 The contact area was 1 kg with a weight of 1 kg. All tests were performed three times and the average values ​​were reported.

[0385] Figure 5 , Figure 6 and Figure 7 The 180° curves on SS, CC and HDPE are shown for the initial and aged samples. o Results of the peel adhesion test. The adhesion values ​​of the resin-based adhesives were comparable to the control-based adhesives within the experimental error involved in the test. The adhesion values ​​of the wax-based adhesives were comparable to the control on CC within the experimental error.

[0386] like Figure 8 , Fig. 9 and Fig.10The circular quick tack data comparing adhesives with resin and wax products from pyrolysis oil polymerization to adhesives with Wingtack 10 show similar performance on SS, HDPE and CC.

[0387] Fig.11 , Fig.12 and Fig.13 The quick tack results and similar performance of the resin and wax based adhesives to the WT10 based adhesives on SS, HDPE and CC are shown. The adhesives formulated with the resin and WT10 exhibited stick slip on SS and HDPE during the quick tack test, while the adhesives formulated with the wax did not have any stick slip on any of the substrates tested. The results from the loop quick tack and quick tack tests indicate that the adhesives formulated with the resin and wax from the pyrolysis oil polymerization have similar tack to the adhesives formulated with WT10.

[0388] The results of room temperature shear tests on SS and kraft paper are shown in Fig.14 and Fig.15 All samples still hanging after 25,000 minutes were removed (pulled out) from the test apparatus and the results reported as 25,000 minutes. The performance of the resin based adhesive was comparable to that of the WT10 based adhesive on both SS and Kraft paper.

[0389] When measured by SAFT, the heat resistance of the adhesive formulated with resin, wax and WT10 showed Fig.16 and Fig.17 Within experimental error, the heat resistance of all three adhesive formulations was identical on SS, and the resin materials were similar on kraft paper.

Claims

1. An adhesive composition comprising an elastomer and one or more tackifying resins, characterized in that One of the one or more tackifying resins comprises a liquid resin prepared by polymerization from liquefied waste polymers, preferably pyrolysis oils.

2. The adhesive composition according to claim 1, characterized in that The elastomer is selected from styrene-isoprene block copolymers, polyacrylate resins, polyethylene vinyl acetate (EVA) resins, polystyrene-butadiene resins, random styrene butadiene (SBR) copolymers, styrene-butadiene block copolymers, styrene-isoprene-butadiene-styrene (SIBS) copolymers, styrene-ethylene-propylene-styrene (SEPS) copolymers, styrene-ethylene-butylene-styrene (SEBS) block copolymers, amorphous poly-olefin (APO) resins, and mixtures thereof.

3. The adhesive composition according to any one of claims 1 or 2, characterized in that The elastomer is present in an amount ranging from 1 to 90% by weight, and / or the tackifying resin derived from liquid waste polymer is present in an amount ranging from 1 to 75% by weight.

4. The adhesive composition according to any one of claims 1 to 3, characterized in that When passing 1 The liquid resin exhibits an olefin content of at most 20.0 wt %; preferably in the range of 0.1 to 10.0 wt % when measured by H NMR.

5. The adhesive composition according to any one of claims 1 to 4, characterized in that When passing 1 The liquid resin exhibits an aliphatic content in the range of 15 to 100 wt %; preferably in the range of 50.0 to 99.0 wt % when measured by H NMR.

6. The adhesive composition according to any one of claims 1 to 5, characterized in that When passing 1 The liquid resin exhibits an aromatic content of less than 50.0 wt %; preferably in the range of 0.1 to 50.0 wt % when measured by H NMR.

7. The adhesive composition according to any one of claims 1 to 6, characterized in that The liquid resin exhibits a viscosity ranging from 10 to 50 000 cps; preferably ranging from 10 to 10 000 cps at 30° C., measured using a Brookfield viscometer.

8. The adhesive composition according to any one of claims 1 to 7, characterized in that The liquid resin exhibits a number average molecular weight (Mn) ranging from 100 to 10 000 g / mol; preferably from 100 to 700 g / mol, measured using gel permeation chromatography and polystyrene calibration.

9. The adhesive composition according to any one of claims 1 to 8, characterized in that The liquid resin comprises a comonomer selected from the group consisting of styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 4-tert-butylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2,4-diisopropylstyrene, 2,4,6-trimethylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, 1-vinylnaphthalene, 2-vinylnaphthalene, vinylanthracene, 4-methoxystyrene, monochlorostyrene, dichlorostyrene, divinylbenzene, indene, methyl-indene, and mixtures thereof; preferably, the liquid resin comprises a comonomer, the comonomer being or comprising styrene.

10. The adhesive composition according to any one of claims 1 to 9, characterized in that The liquid resin comprises a comonomer present in a concentration ranging from 0.01 to 90 mol %, preferably 1.0 to 80 mol %, based on the total weight of the liquid resin.

11. The adhesive composition according to any one of claims 1 to 10, characterized in that It is a wax and / or it exhibits a crystallization temperature (Tc) below 35°C; preferably in the range of 20 to 30°C.

12. The adhesive composition according to any one of claims 1 to 10, characterized in that It is a resin and / or it exhibits a glass transition temperature (Tg) below -20°C; preferably in the range of -50°C to -30°C, when measured by differential scanning calorimetry.

13. An article comprising a substrate and the adhesive composition according to any one of claims 1 to 12, the adhesive composition being applied to at least one surface of the substrate, wherein the substrate is selected from the group consisting of a tape and a label.

14. A coated article comprising the adhesive composition according to any one of the preceding claims 1 to 12; the adhesive composition being applied to at least one of wood, nonwoven fabrics, and book bindings.

15. A box and case assembly line comprising an adhesive station, wherein the adhesive station dispenses the adhesive composition according to claims 1 to 12.

16. A process for preparing a liquid resin from liquefied waste polymers, the liquid resin being an oligomeric product and suitable for preparing an adhesive composition according to any one of claims 1 to 12, or suitable for any product according to any one of claims 13 to 15, the process being characterized by the following steps: a) providing a feed stream (1) containing liquefied waste polymer, wherein the feed stream (1) contains at least 0.1 wt. % to at most 80 wt. % of dienes, based on the total weight of the feed stream (1); c) polymerizing the feed stream (1) under polymerization conditions to obtain a first product stream (3) comprising oligomeric products (33) and purified liquefied waste polymer; d) optionally, conducting a neutralization reaction by contacting the first product stream (3) with a basic compound (25) to obtain a neutralized product stream (4), and removing the basic compound from the neutralized product stream (4) to obtain a second product stream (5); g) separation to separate the oligomeric product (33) from the purified liquefied waste polymer (34).

17. The process according to claim 16, characterized in that The polymerization reaction in step c) is a cationic polymerization; and / or the process further comprises a step (b) of drying the feed stream (1) to obtain a dried feed stream (2), wherein step b) is carried out before step c) of polymerization, so that step c) of polymerization is carried out on the dried feed stream (2).

18. The process according to claim 17, characterized in that A drying step b) is performed, and step b) comprises a sub-step b1) of decantation and / or centrifugation; preferably, the first sub-step b1) is followed by a second sub-step b2) of drying using molecular sieves to reach a water content of less than 0.1% by volume according to ASTM D95-13 (2018).

19. The process according to any one of claims 16 to 18, characterized in that The feed stream contains at least 75 wt% of liquefied waste polymer, based on the total weight of the feed stream; and / or the polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst; preferably, the acidic catalyst is a Bronsted acid or a Lewis acid.

20. The process according to claim 19, characterized in that The polymerization reaction in step c) is a cationic polymerization carried out in the presence of an acidic catalyst, wherein the acidic catalyst is a Lewis acid selected from BF3, a complex of boron trifluoride, AlCl3, SnCl4, ZnCl2, FeCl3 and TiCl3, an alkylaluminum chloride, H2SO4, or any mixture thereof; preferably, the acidic catalyst is or comprises boron trifluoride etherate.

21. The process according to claim 19 or 20, characterized in that The acidic catalyst is present in a concentration ranging from 0.5 wt % to 5.0 wt %, based on the total weight of the feed stream (1), and / or the polymerization reaction of step c) is carried out until the diene content of the purified liquefied waste polymer is less than 5.0 wt %, based on the total weight of the first product stream (3).

22. The process according to any one of claims 16 to 21, characterized in that The polymerization conditions of step (c) include a contact time ranging from 5 minutes to 5 hours; and / or a temperature ranging from 5 to 100° C. at atmospheric pressure.

23. The process according to any one of claims 16 to 22, characterized in that The polymerization reaction of step c) is carried out in the presence of one or more comonomers; preferably, the one or more comonomers comprise vinyl aromatic and / or the one or more comonomers are present in a concentration of 1.0 to 25.0 wt %, based on the total weight of the liquefied waste polymer.

24. The process according to any one of claims 19 to 23, characterized in that Step d) is carried out with a concentration of the basic compound in the range of 0.1 to 50.0% by weight, based on the total weight of the neutralized product stream (4).

25. The process according to any one of claims 19 to 24, characterized in that Step d) is carried out and the basic compound: - has a pKa in water in the range of 7.5 to 14; and / or - is selected from LiOH, NaOH, CsOH, Ba(OH)2, Na2O, KOH, K2O, CaO, Ca(OH)2, MgO, Mg(OH)2, NH4OH, or any mixture thereof.

26. The process according to any one of claims 19 to 25, characterized in that Step d) is performed in continuous mode, and / or step d) is performed and the basic compound is removed from the neutralized product stream (4) to obtain a second product stream (5) by decantation and / or by centrifugation.

27. The process according to any one of claims 16 to 26, characterized in that It further comprises a step e) of washing the first product stream (3) or the second product stream (5) with a solvent (27) to obtain a washed stream (6); preferably, the washing is carried out at a temperature ranging from 5°C to 95°C.

28. The process according to claim 27, characterized in that The solvent (27) is selected from water or an acidic aqueous solution, wherein the acidic aqueous solution contains one or more selected from citric acid ( )、Formic acid( ), acetic acid ( ), aminosulfonic acid ( ), and any combination thereof, and / or one or more inorganic acids selected from hydrochloric acid (HCl), nitric acid (HNO3), sulfuric acid (H2SO4), phosphoric acid (H3PO4), and any combination thereof.

29. The process according to claim 27 or 28, characterized in that The washing is performed until the pH of the washed stream (6) is in the range of 5.0 to 9.0; and / or the washing is followed by decantation and / or centrifugation to separate the solvent from the washed stream (6).

30. The process according to any one of claims 16 to 29, characterized in that It further comprises a step f) of filtering the stream obtained in the previous step to obtain a filtered stream (7), wherein the filtration is carried out to remove solids from the first product stream (3) or from the second product stream (5) or from the washed stream (6), and / or to agglomerate remaining traces of solvent, if any; preferably, the filtration step is followed by a dehydration step.

31. The process according to any one of claims 16 to 30, characterized in that The step g) of separating is carried out via distillation or steam distillation or vacuum stripping or fractional distillation or any combination thereof.

32. The process according to any one of claims 16 to 31, characterised in that After separation step g), the purified liquefied waste polymer is collected and blended in a fuel pool; preferably, the purified liquefied waste polymer is separated into a naphtha fraction having a boiling range of less than 150°C and a diesel fraction having a boiling range between 150 and 350°C, wherein the naphtha fraction is incorporated into the naphtha pool and the diesel fraction is incorporated into the diesel pool.

33. The process according to any one of claims 16 to 32, characterised in that The liquefied waste polymer is pyrolyzed plastic oil. Preferably, step a) of providing a feed stream (1) containing the liquefied waste polymer comprises a preliminary step of preparing the liquefied waste polymer, comprising: a1) Provide waste plastic streams; a2) pyrolyzing the waste plastic stream at a temperature of at least 200° C.; a3) collecting the pyrolyzer effluent and separating it into a C1 to C4 hydrocarbon fraction, a fraction having a boiling range above 350° C., and a remaining fraction as the pyrolyzed plastic oil; a4) optionally sending the fraction with a boiling range above 350°C to a fluid catalytic cracking unit, or a hydrocracking unit, a coker, or a visbreaker, or blending said fraction with a boiling range above 350°C in crude oil or in a crude oil fraction for further refining.

34. The process according to any one of claims 16 to 33, characterised in that The liquefied waste polymer in the feed stream (1) has a final boiling point of at most 700°C; and / or the feed stream (1) contains 0.1 to 25.0 wt. % of diene, based on the total weight of the feed stream (1).

Citation Information

Patent Citations

  • Process for producing resins from rubber chips

    FR3116279A1

  • Game system, and control method of controlling computer and storage medium storing computer program used thereof

    US20120214592A1

  • Conversion of plastics to olefin and aromatic products with product recycle

    US20140228606A1

  • Conversion of plastics to olefin and aromatic products

    US8895790B2

  • Upgrading hydrogen deficient streams using hydrogen donor streams in a hydropyrolysis process

    WO2016009333A1